(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
It is known that mathematical modeling plays an important role in many fields - from physics and engineering to biology and economics. This article examines information technologies used to create, visualize, and analyze mathematical models. Various types of technologies, including graphical interfaces, computational algorithm libraries, big data and machine learning technologies, as well as interactive web applications, are described. The article also provides practical examples of using information technology in various industries where mathematical modeling is used.